DYNAMIC CHANGES IN EUSTACHIAN TUBE FUNCTION IN PATIENTS WITH CHRONIC TUBOTYMPANIC SUPPURATIVE OTITIS MEDIA AFTER TYMPANOPLASTY USING VENTILATION TUBES ACCORDING TO THE INFLATION- DEFLATION TEST - Гринько I.I. (The Ukrainian Scientific Medical Youth Journal, 2019)
In the treatment of chronic tubotympanic suppurative otitis media, one of the main conditions for a successful treatment is a sufficient function of the Eustachian tube (ET). Earlier, the 5th grade of ET function was considered as a contraindication for tympanoplasty. The inflationdeflation test allows accurately assess the degree of dysfunction of the ET and optimize surgical tactics. We examined 49 patients with 5th grade of ET function aged 19 to 56 years, 30 were women and 19 men. At the 5th grade of ET function, the result was interpreted as abnormal (dysfunction of the ET) - patients underwent tympanoplasty with Teflon or silicone VT. Inflation-deflation test was performed in all patients postoperatively after 3, 6, 12 months. With the improvement of ET function (changing grade from 5th to 1-4th, the VT was removed). Was found that in men, the 5th grade of ET dysfunction is observed less often (37.5%) than in women (52.6%). Improvement of ET function in patients with teflon VT is faster than in patients with silicone VT. At the same time, restoration of the tympanic membrane leads to decrease of the 5th grade of the ET function when comparing between the 3rd and 6th and 12th months, and also between the 6th and 12th months after surgery in both groups of men and women.